2015
DOI: 10.1002/jcp.24856
|View full text |Cite
|
Sign up to set email alerts
|

TGFβ3 Regulates Periderm Removal Through ΔNp63 in the Developing Palate

Abstract: The periderm is a flat layer of epithelium created during embryonic development. During palatogenesis, the periderm forms a protective layer against premature adhesion of the oral epithelia, including the palate. However, the periderm must be removed in order for the medial edge epithelia (MEE) to properly adhere and form a palatal seam. Improper periderm removal results in a cleft palate. Although the timing of transforming growth factor β3 (TGFβ3) expression in the MEE coincides with periderm degeneration, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
48
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(53 citation statements)
references
References 67 publications
3
48
0
2
Order By: Relevance
“…As p63 expression is maintained in the MEE of Tgfb3 -/- mice which exhibit cleft palate and persistent periderm cells over the MEE [12,19,23,24], we manipulated the level of p63 in the MEE of Tgfb3 -/- mice genetically. Initially, we generated Tgfb3 +/- ; p63 +/- compound heterozygous mice which did not exhibit any gross abnormalities and in which fusion of the secondary palate proceeded normally.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…As p63 expression is maintained in the MEE of Tgfb3 -/- mice which exhibit cleft palate and persistent periderm cells over the MEE [12,19,23,24], we manipulated the level of p63 in the MEE of Tgfb3 -/- mice genetically. Initially, we generated Tgfb3 +/- ; p63 +/- compound heterozygous mice which did not exhibit any gross abnormalities and in which fusion of the secondary palate proceeded normally.…”
Section: Resultsmentioning
confidence: 99%
“…During palatogenesis in wild-type embryos, confocal imaging of GFP expression over a 24-hour period revealed that periderm cells migrated out of the MEE towards the epithelial triangles and into the oral and nasal epithelia of the palatal shelves allowing MES degradation to be completed (S1 Video). As p63 is down-regulated in the MEE of wild-type but not Tgfb3 -/- mice which exhibit cleft palate and persistent periderm cells over the MEE [12,19], we crossed the mKrt17 -GFP reporter onto a Tgfb3 -/- background and noted that GFP-labelled periderm cells failed to migrate out of the MEE despite forced contact between the palatal shelves (Fig 2D–2F; S2 Video). In contrast, the migratory periderm phenotype observed in the MEE of wild-type mice was restored in Tgfb3 -/- ; p63 +/- embryos (Fig 2G–2I; S3 Video).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…TGF-b, Shh, BMP, and Wnt signaling pathways have all been considered to contribute to palatal morphogenesis [2]. TGF-b3, which plays an essential role in palatogenesis, has been extensively studied [6]. It has been proposed that the MES independently but sequentially undergoes cell cycle arrest, cell migration, and apoptosis following the treatment of isolated MES cells with TGF-b3 [7].…”
Section: Introductionmentioning
confidence: 99%